Plasma Epstein-Barr Virus DNA load for diagnostic and prognostic assessment in intestinal Epstein-Barr Virus infection - Chunxiang Ma; Chunxiang Ma; Chunxiang Ma; Mingshan Jiang; Mingshan Jiang; Mingshan Jiang; Jiaxin Li; Jiaxin Li; Jiaxin Li; Zhen Zeng; Zhen Zeng; Zhen Zeng; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundThe prospective application of plasma Epstein-Barr virus (EBV) DNA load as a noninvasive measure of intestinal EBV infection remains unexplored. This study aims to identify ideal threshold levels for plasma EBV DNA loads in the diagnosis and outcome prediction of intestinal EBV infection, particularly in cases of primary intestinal lymphoproliferative diseases and inflammatory bowel disease (IBD).MethodsReceiver operating characteristic (ROC) curves were examined to determine suitable thresholds for plasma EBV DNA load in diagnosing intestinal EBV infection and predicting its prognosis.Results108 patients were retrospectively assigned to the test group, while 56 patients were included in the validation group. Plasma EBV DNA loads were significantly higher in the intestinal EBV infection group compared to the non-intestinal EBV infection group (Median: 2.02 × 102 copies/mL, interquartile range [IQR]: 5.49 × 101-6.34×103 copies/mL versus 4.2×101 copies/mL, IQR: 1.07 ×101-6.08×101 copies/mL; P < 0.0001). Plasma EBV DNA levels at 9.21×101 and 6.77×101 copies/mL proved beneficial for the identification and prognostication in intestinal EBV infection, respectively. Values of 0.82 and 0.71 were yielded by the area under the ROC curve (AUC) in the test cohort, corresponding to sensitivities of 84.38% (95% confidence interval [95%CI]: 68.25%-93.14%) and 87.5% (95%CI: 69%-95.66%), specificities of 83.33% (95%CI: 64.15%-93.32%) and 68.09% (95%CI: 53.83%-79.6%), positive predictive values (PPV) of 87.1% (95%CI: 71.15%-94.87%) and 58.33% (95%CI: 42.2%-72.86%), and positive likelihood ratios (LR+) of 5.06 and 2.74 in the validation cohort, respectively. Furthermore, a plasma EBV DNA load of 5.4×102 copies/mL helped differentiate IBD with intestinal EBV infection from primary intestinal EBV-positive lymphoproliferative disorders (PIEBV+LPDs), achieving an AUC of 0.85 within the test cohort, as well as 85% sensitivity (95%CI: 63.96%-94.76%), 91.67% specificity (95%CI: 64.61%-99.57%), 94.44% PPV (95%CI: 74.24%-99.72%), and an LR+ of 10.2 in the validation cohort.ConclusionsPlasma EBV DNA load demonstrates notable potential in distinguishing between different patient cohorts with intestinal EBV infection, although its sensitivity requires further optimization for clinical application.